Her kind of want - Davis, Jennifer S., 1973- (Iowa short fiction award., 2002)
Set mainly in the small towns of Alabama, the stories in Her Kind of Want ache with the relentless longing of the poor, struggling, usually discarded southern women who tell us their lives--lives that seem to revolve around men whose only presence is their absence.